Analisis Implementasi Permenaker Nomor 6 Tahun 2020 dalam Program Pemagangan Di Sektor Industri - Kurnia, Hendra; Indriani, Ria; Septiani, Tiara Tri; Azahra, Vinie; Pamungkas, Bayu Alam (Journal of Industrial Relations Studies, 2025)
Internships are crucial for developing human resources (HR) in Indonesia, bridging the gap between education and industry. This study examines the implementation of Regulation No. 6 of 2020 by the Ministry of Manpower concerning domestic internships in Karawang, West Java. A descriptive qualitative approach was used to explore policy execution, challenges, and success factors. The findings reveal that while many companies comply with the regulation, challenges persist, such as limited understanding of regulations, weak supervision, and inadequate training facilities. Additional obstacles include mismatches between educational curricula and industry needs and infrastructure constraints in small and medium enterprises. Recommendations include strengthening supervision, providing incentives to companies, and enhancing collaboration between education and industry. These improvements aim to make internship programs more effective in enhancing workforce skills and increasing Indonesia's competitiveness in the global market